1984
DOI: 10.1159/000466281
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Example of Weakened Expression of the Kell (K1) Antigen

Abstract: Random typing of donor units revealed a donor whose red blood cells gave very weak reactions with all anti-Kell (anti-K1) antisera. All other Kell-system antigens (including Kx) and antigens of other red-cell systems tested were normal. This weak K1 antigen was present in four generations of the donor’s family. The red-cell morphology is normal in all family members with the weakened K1 antigen. A consistent hypothesis is that the weak antigen is inherited through a variant allele at the Kell locus and represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…KEL1, the original Kell antigen, is no exception. There is one report of an apparent qualitative KEL1 variant in a KEL:1 individual with a KEL1‐like antibody 11 and two other reports of weak or variant KEL1 that were not associated with anti‐KEL1 production 12,13 . None of these variants was investigated at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…KEL1, the original Kell antigen, is no exception. There is one report of an apparent qualitative KEL1 variant in a KEL:1 individual with a KEL1‐like antibody 11 and two other reports of weak or variant KEL1 that were not associated with anti‐KEL1 production 12,13 . None of these variants was investigated at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…In other rare cases, red cells have a diminished expres sion of one of the Kell antigens while the others have a nor mal expression [12,39], We have sequenced KEL DNA from one such individual. DNA from a person expressing weak KEL2 had a C1388T mutation in exon 11 leading to an alanine to valine change at residue 423 [unpubl.…”
Section: Kel23mentioning
confidence: 99%
“…An\ Bgabc, Bpa, Bxa, By\ Crawford, Dha, Fra, Hga, Hov/Wu, Ina, JFV, Lsa, Moa, Or, Osa, Pta, RASM, Rba, Rda, Ska, Swa, Toa, Tra, Vga, Wb, Wda, WESa. AL's serum was also tested with RBCs from the donor described by Kline et al [3]. The reactivity with this donor's RBCs was significantly less than with JC's or K:l,2 RBCs.…”
Section: Methodsmentioning
confidence: 99%
“…Hawley et al [2] described a donor whose RBCs were not agglutinated by any anti-Kl but did absorb and elute some examples of anti-Kl, imply ing a quantitative and qualitative change in the Kl anti gen. Kline et al [3] reported a donor whose RBCs were agglutinated weakly by all anti-Kl sera tested. This weak Kl antigen was present on RBCs in 4 generations and represents a quantitative change.…”
Section: Introductionmentioning
confidence: 99%